Study the Geotechnical Properties for Recent Deposits/AL-Fursan Area North of Tikrit - Salih Rakan Shalal; Mohammed Rashid Abood; Amera Ismail Hussain (Tikrit Journal of Pure Science)
Four sites with different depth in AL-Fursan area/ North Tikrit city were selected for recent deposits sampling. The geotechnical properties of soil were tested and improvement of engineering properties of soil by cement was carried out. The geotechnical properties  test results revealed that the moisture content ranges between (0.53 -1.45)% which is low because of  sampling in summer season, while the grain size analysis show that the soil at the study area is coarse soil (sand) with fines. The soil type in the first site is clayey sand (SC), the second site contains sand with equal percentage of silt and clay (SC- SM) , the third and fourth site types are silty sand (SM). The specific gravity ranges between (2.46- 2.72) sites (1,2,3) are low liquid limit and low swelling index but the fourth site is moderate. The value of cohesion strength for the four sites are (16, 13, 1, 8)kPa respectively, sites (1) and (2)  are moderate cohesion while sites (3) and (4) are non-cohesion, none plastic and un active.